ANALISIS KEMAMPUAN BERARGUMENTASI ILMIAH SISWA SMA PADA KONSEP TERMODINAMIKA - Nata Amalia Sudarmo; Albertus Djoko Lesmono; Alex Harijanto (JURNAL PEMBELAJARAN FISIKA, 2018)
ABSTRACT Education plays a role and a very important factor in human life. Since formaleducation applies new curriculum which is curriculum 2013, it causes the students tohave less capability to make the argumentations toward the learning material. Thefacts on the real situation show that the ability to make argumentations about thesubject of physics on the concept of thermodynamics among students is still very low.So a scientific argument test is needed to find out how well the students’ understandingof physics material. Furthermore, by looking at how the students make theargumentations related to thermodynamic material, it will make the teacherunderstands the level students’ understanding of thermodynamic material. The resultof data analysis and discussion concluded that the percentage of of the level ofstudents’ scientific argumentation ability on the concept of thermodynamics in SMAX has the highest average of 41.60% based on indicator of argumentation’s proofwhich reaches the High criterion (T) and the highest average level of 51.96% basedon indicator of argumentation’s justification which meets the Medium criteria (S). Key word: Education, Science Argumentation, Thermodynamic Concept